O impacto dos gastos públicos no Indice de Desenvolvimento Humano: o caso dos municípios do Ceará - Nova, Milton Jaques da (2006)
This research examines the impact of the public expenditure on the Human Development Index – HDI of municipalities in Ceara State. This study discusses the concepts and quantitative ways of measuring human development and welfare. It also presents an overview of the impact of the poverty eradication policies on welfare at the national level and also in Ceara State. It is developed and estimated an econometric model to assess how public expenditure impacts the HDI. The main conclusion of this study is that total expenditure has only a weakly influence on the IDH, while public expenditures on education and housing have a positive and statistically significant impact on the HDI. This finding has important policy implication since it may help policymakers to design and implement public policies.